Sustainable solid waste management in sub-Saharan African cities: application of system thinking and system dynamic as methodological imperatives in Kinshasa, the Democratic Republic of Congo. Issue 2 (1st February 2018) - Kubanza, Nzalalemba Serge; Simatele, Danny
ABSTRACT: This paper is based on a review of the methodological approaches associated with solid waste management (SWM) in the context of sub-Saharan African (SSA) cities. Using Kinshasa, the capital of the Democratic Republic of the Congo, as a case study, the paper proposes a new way of looking at solid waste in the bid to come up with alternative methods to improve the plight of SWM. A combination of qualitative research methods and system analysis have been employed to evaluate the causal relationships observed in contemporary SWM systems in Kinshasa. This paper argues that there is an absence of coherent and broad-based approaches to SWM in Kinshasa as is common in other SSA countries. Empirical evidence suggests that contemporary SWM strategies and approaches developed on a global scale which have increasingly been adopted by the Congolese national and local government authorities have proven inadequate to address the SWM realities on a local level. Using system thinking and system dynamics, this paper attempts to develop a feasible methodological framework focusing on the formulation of an appropriate approach to improve SWM in Kinshasa. It is argued that new ways of approaching the complexity that exists in SWM will facilitate the adoption of technologies and innovative ways of thinking and managing solid waste in a more sustainable, socially, and environmentally accepted manner.